The Dual Role of Oyster Seekers in Improving The Family Economy in Alue Naga Village, Syiah Kuala District, Banda Aceh City - Suri Purnama Febri; Suraiya Nazlia; Karimullah Karimullah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
Women in the village in Alue Naga Village working as domestic workers do not bring direct results such as looking after children. On the other hand, in accordance with the development of society, especially in the economic sector, the role of women as workers in the field of breadwinner is clearly visible. The research method used in this research is a survey method. Respondents were determined using the snowbell sampling method. The results showed that the cause of women looking for oysters to play a dual role is internal factors, namely the husband's income is not sufficient for daily living needs, coupled with expenses and number of dependents in the family, external factors, namely the surrounding environment in the form of coastal areas where many women look for oysters, education low level do not have sufficient skills so that there are no opportunities for other work. The form of dual roles, namely as mother, caring for children and husband, as wife, educating children and the economy. The impact of the dual role for the family is difficulty in carrying out their domestic duties, less optimal time they have to share the roles they play, fatigue in activities in their work professionally, and complaints that are felt by wives towards their husbands when they are tired at work.